Effects of Visual Priming and Event Orientation on Word Order Choice in Russian Sentence Production - Pokhoday, Mikhail; Shtyrov, Yury; Myachykov, Andriy (Frontiers in Psychology, 2019)
Existing research shows that distribution of the speaker’s attention among event’s protagonists affects syntactic choice during sentence production. One of the debated issues concerns the extent of the attentional contribution to syntactic choice in languages that put stronger emphasis on word order arrangement rather than the choice of the overall syntactic frame. To address this, the current study used a sentence production task, in which Russian native speakers were asked to verbally describe visually perceived transitive events. Prior to describing the target event, a visual cue directed the participants’ attention to the location of either the agent or the patient of the subsequently presented visual event. In addition, we also manipulated event orientation (agent-left vs agent-right) as another potential contributor to syntactic choice. The number of patient-initial sentences was the dependent variable compared between conditions. First, the obtained results replicated the effect of visual cueing on the word order in Russian language: more patient-initial sentences in patient cued condition. Second, we registered a novel effect of event orientation: Russian native speakers produced more patient-initial sentences after seeing events developing from right to left as opposed to left-to-right events. Our study provides new evidence about the role of the speaker’s attention and event orientation in syntactic choice in language with flexible word order.